Pembelajaran Computer Assisted Instruction Untuk Meningkatkan Hasil Belajar IPA - Haryanto, Mursis (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
The teaching media taken in this study is Computer Media. This study aims to describe whether the use of computers will improve learning activities and outcomes. Data collection techniques in this study were in the form of tests of student learning outcomes using tests, and observation sheets to find out student learning activities, as well as documentation. Judging from the average learning outcomes there is an increase shown from the average value in the first cycle is 67.78 to 80 in the second cycle. This means an increase of 12.22. From the results of the analysis it can be concluded that the use of computers in science learning can improve student learning outcomes. This can be seen from the percentage of students who complete learning in the first cycle and second cycle. Based on the above data, researchers can provide answers to the hypothesis of action in the research that has been carried out.